Therapeutical Intervention, Relaxation, Mental Images, and Spirituality (RIME) for Spiritual Pain in Terminal Patients. A Training Program - Ana Catarina de Araújo Elias; Joel Sales Giglio; Cibele Andrucioli de Mattos Pimenta; Linda Gentry El-Dash (The Scientific World Journal)
Therapeutic intervention involving the technique of Relaxation, Mental Images, and Spirituality (RIME) can foster the redefinition of spiritual pain in terminal patients. A training course was developed to instruct health care professionals in its use, and the results were followed up by evaluating reactions of professionals to its use in intervention with patients. Six subjects (a nurse, a doctor, three psychologists, and an alternative therapist), all skilled in palliative care, were invited to take part in the experience. They worked with 11 terminal patients in public hospitals of the cities of Campinas, Piracicaba, and São Paulo, located in Brazil. The theoretical basis for the study involves action research and phenomenology, and the results were analyzed using both qualitative and quantitative methods. The analysis of the experience of the professionals revealed 5 categories and 15 subcategories. The analysis of the nature of spiritual pain revealed 6 categories and 11 subcategories. The administration of RIME revealed statistically significant differences (p < 0.0001), i.e., patients reported a greater level of well-being at the end than at the beginning of sessions, which suggests that RIME led to the redefinition of spiritual pain for these terminal patients. The training program proposed has shown itself to be effective in preparing health care professionals for the use of RIME intervention.